A Case of Undulating Fevers and Elevated Liver Tests after Pancreas–Kidney Transplantation - Im, Gene Y.; Sehgal, Vinita; Ward, Stephen C. (Seminars in Liver Disease, 2013)
The patient is a 50-year-old Caucasian woman with a history of a pancreas and two kidney transplants complicated by chronic rejection of her latest kidney allograft and currently undergoing hemodialysis, who was referred for fever of unknown origin and elevated liver tests. She suffered a self-limited acute diarrheal illness with fever 3 months prior to referral and then experienced a persistent, undulating fever pattern. An exhaustive evaluation involving many consultants was undertaken, but failed to determine the etiology of her symptoms. Given her history, persistently elevated liver tests, and abnormal but nonspecific liver biopsy findings, infection with hepatitis E virus (HEV) was entertained. Several serum and stool samples were sent to the Centers for Disease Control for detection of HEV that were positive and ultimately consistent with autochthonous chronic HEV infection. The patient was treated with ribavirin and achieved normalization of her transaminase activities and resolution of her fever after 1 month, and undetectable HEV polymerase chain reaction at treatment month 6 and 10, at which time treatment was stopped. There has been renewed interest in HEV in light of recent studies demonstrating the existence of a chronic form of HEV infection occurring in immunosuppressed patients, such as solid-organ-transplant recipients. This report highlights a case of chronic HEV infection in a pancreas–kidney-transplant recipient with an unusual clinical presentation and highlights the need for increased awareness of chronic HEV infection in the hepatology and transplant community.
Keywords: hepatitis E virus; HEV; chronic hepatitis E; fever of unknown origin; hepatitis; pancreas–kidney transplantation; elevated liver tests; immunosuppression